Targeting Heme with Single Domain Antibodies - Gouveia, Zélia Lícinia Ferreira (2018)
Heme, i.e. iron (Fe) protoporphyrin IX, functions as a prosthetic group in a variety of hemoproteins that participate in vital biologic functions essential to sustain life. Heme is a highly reactive molecule, participating in redox reactions, and presumably for this reason it must be sequestered within the heme pockets of hemoproteins, controlling its reactivity. However, under biological stress conditions, hemoproteins can release their prosthetic groups, generating “free heme”, which binds loosely to proteins or to other molecules and presumably acquires unfettered redox activity. Moreover, a growing body of evidence supports the notion that “free heme” can act in a vasoactive, pro-inflammatory and cytotoxic manner when released from a subset of these hemoproteins, such as extracellular hemoglobin, generated during hemolytic conditions. (...)